The Influence of Shopping and Gender Differences on Online Shopping - Khusaini Khusaini; Heni Cahya Ramdani; Riski Ambarumanti (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
This study aims to analyze the influence of shopping and gender orientation on online shopping, and analyze the differences in shopping orientation and online shopping between men and women. The sample in this study were 151 UNIS Tangerang students. The analysis method uses multiple linear regression test. Furthermore, this study also uses independent sample T test to analyze differences in shopping orientation and online shopping for male and female students. In shopping orientation, use shopping enjoyment indicators, fashion / conscious, price conscious, shopping confidence, time conscious, in-home shopping tendency, brand/store loyalty. The results showed that partially, shopping orientation had a significant effect on online shopping but there was no gender influence on online shopping. And simultaneously shows that shopping orientation and gender have a significant effect on online shopping. The results show that there is no difference between men and women in shopping orientation and online shopping.